Pathways to and factors associated with rape stigma experienced by rape survivors in South Africa: Analysis of baseline data from a rape cohort - Jewkes, R.; Mhlongo, S.; Chirwa, E.; Seedat, S.; Myers-Franchi, Bronwyn; Peer, N.; Garcia-Moreno, C.; Dunkle, K.; Abrahams, N. (WILEY, 2021)
Rape stigma, both external and self-stigmatization (self-blame), is associated with adverse health outcomes. Understanding its origins and resilience factors is critical for reducing and preventing it. We describe the prevalence of rape stigma, the characteristics of women experiencing it and the pathways to experiencing greater stigma. The Rape Impact Cohort Evaluation study enrolled 852 women aged 16–40 years who had been raped from post-rape care centres in Durban, South Africa. We present a descriptive analysis of the baseline data, a multinomial logistic regression model of factors associated with different levels of stigma and a structural equation model (SEM). Most women reported stigmatizing thoughts or experiences, with self-stigmatizing thoughts being more prevalent than external stigmatization. The multinomial model showed that experiences of childhood or other trauma, emotional intimate partner violence (IPV), having less gender equitable attitudes and food insecurity were significantly associated with medium or high versus low levels of stigma. Internal and external stigma were significantly associated with each other. Women who had been previously raped reported less stigma. The SEM showed a direct path between food insecurity and rape stigma, with poorer women experiencing more stigma. Indirect paths were mediated by more traditional gender attitudes and childhood trauma experience and other trauma exposure. Our findings confirm the intersectionality of rape stigma, with its structural drivers of food insecurity and gender inequality, as well as its strong association with prior trauma exposure. Rape survivors may benefit from gender-empowering psychological support that addresses blame and shame.